P10 The Effect Of Naltrexone, An Opioid Receptor Antagonist, On Capsaicin Evoked Cough, In Healthy Male Subjects. (10th November 2014) - Satia, I; Holt, K; Hilton, E; Woodcock, AA; Smith, J
Abstract : Introduction: Chronic cough is a troublesome condition that reduces patient quality of life. Recent evidence suggests that healthy females cough more than healthy males but the mechanism underlying this in unclear. 1 We hypothesise that opiate-sensitive inhibitory control mechanisms determine capsaicin-evoked cough responses in healthy subjects. Aim: To show that in healthy males the number of capsaicin-evoked coughs is increased following administration of naltrexone, an opiate receptor antagonist, compared with placebo. Method: 15 male subjects (median age 30 yrs (21–59)) were recruited in to a randomised double blind cross-over trial of single doses of naltrexone vs. placebo given 1 week apart. A capsaicin inhalational challenge (doubling doses 0.48 to 125[micro]M) was performed 60 min after ingestion of naltrexone/placebo using a dosimeter. Four inhalations 30 seconds apart were performed at each concentration and the total coughs evoked at each dose were recorded and verified using a cough monitor. Results: There was a tendency for subjects to cough more when treated with naltrexone (16.7 ± 2.7 (SEM) compared with placebo (13.7 ± 1.6), (p = 0.11, general estimating equations). See Figure 1 Conclusion: This small pilot study suggest that opiate sensitive inhibitory mechanisms may have a role in controlling the cough reflex even in healthy subjects. References: Hilton EC, Baverel PG, Woodcock A, Van Der Graaf PH, Smith JA. J Allergy Clin Immunol . 2013 Oct;132(4):847–55